Assessing the Longer Term Impact of Community-Driven Development Programs : Evidence from a Field Experiment in the Democratic Republic of Congo - Mvukiyehe, Eric (World Bank, Washington, DC, 2020)
Community-driven development programs are a popular model for service delivery and socioeconomic development, especially in countries reeling from civil strife. Despite their popularity, the evidence on their impact is mixed at best. Most studies thus far are based on data collected during, or shortly after, program implementation. Community-driven development's theory of change, however, allows for a longer time frame for program exposure to produce impact. This study examines the longer term impact of a randomized community-driven development program implemented in 1,250 villages in Eastern Democratic Republic of Congo between 2007 and 2012. The study team returned to these villages in 2015, eight years after the onset of the program. The study finds evidence of the physical endurance of infrastructure built by the program. However, it finds no evidence that the program had an impact on other dimensions of service provision, health, education, economic welfare, women's empowerment, governance, and social cohesion. These findings suggest that, although community-driven development programs may effectively deliver public infrastructure, longer term impacts on economic development and social transformation appear to be limited.